Investigations into the Synthetic Modifications of Terpenes for the Synthesis of Renewable Polyesters - Thomsett, Megan (2019)
This thesis details the synthesis of four novel terpene-derived monomers via the derivatisation of a-pinene and limonene (two of the most abundant terpenes). The monomers have been used in the synthesis of sustainable polyesters, which all contain a unique cyclohexane ring in their backbone.